Crystal structure of copper perchlorophthalocyanine analysed by 3D electron diffraction. Issue 4 (28th July 2021) - Gorelik, Tatiana E.; Habermehl, Stefan; Shubin, Aleksandr A.; Gruene, Tim; Yoshida, Kaname; Oleynikov, Peter; Kaiser, Ute; Schmidt, Martin U.
Abstract : The structure of copper perchlorophthalocyanine (CuC32 N8 Cl16, Pigment Green 7) was solved from three‐dimensional electron diffraction data (3D ED) and placed into the series of known copper phthalocyanine crystal structures. Abstract : Copper perchlorophthalocyanine (CuPcCl16, CuC32 N8 Cl16, Pigment Green 7) is one of the commercially most important green pigments. The compound is a nanocrystalline fully insoluble powder. Its crystal structure was first addressed by electron diffraction in 1972 [Uyeda et al. (1972). J. Appl. Phys. 43, 5181–5189]. Despite the commercial importance of the compound, the crystal structure remained undetermined until now. Using a special vacuum sublimation technique, micron‐sized crystals could be obtained. Three‐dimensional electron diffraction (3D ED) data were collected in two ways: (i) in static geometry using a combined stage‐tilt/beam‐tilt collection scheme and (ii) in continuous rotation mode. Both types of data allowed the crystal structure to be solved by direct methods. The structure was refined kinematically with anisotropic displacement parameters for all atoms. Due to the pronounced crystal mosaicity, a dynamic refinement was not feasible. The unit‐cell parameters were verified by Rietveld refinement from powder X‐ray diffraction data. The crystal structure was validated by many‐body dispersion density functional theory (DFT) calculations. CuPcCl16 crystallizes in the space group C 2/ m ( Z  = 2), with the molecules arranged in layers. The structure agrees with that proposed in 1972.